Knowledge about Human Papilloma Virus (HPV) and HPV Vaccine at Reproductive Age in Primary Care - Ozde Onder (Çukurova Üniversitesi Tıp Fakültesi Dergisi, 2015)
Purpose: The aim of this study was to identify the knowledge and awareness about human papilloma virus (HPV) and human papilloma virus (HPV) vaccine of women in reproductive age. Material and Methods: The study covered 294 women aged between 15 and 49. A questionnaire was prepared by the researchers based on the literature review. Results: The mean age of the participants was 30.5+/-8.9 years. Only 24.5% had heard about HPV infection and 28.2% had heard HPV vaccine. Of the participants, 188 (63.9%) got zero point from the knowledge questions. Conclusion: This study indicates that the women who apply primary care units have low knowledge levels; it is apperent that personal and social education is needed. Paying importance to patient education on HPV and cervical cancer in primary care health politics will increase knowledge and awareness for HPV infection and HPV vaccination. [Cukurova Med J 2015; 40(3.000): 517-524]